Beau Clayton: capstone - Clayton, Beau, artist (Colorado State University. Libraries, 2015)
The artist's statement: I make art because I know that it will make a difference. That seems trivial and cliché, but I make art because I want to see a world where everyone is respected and valued for who they are and what they bring to the table. We live in a society where people are perpetually being scrutinized for who they are. I want to be a voice for those who may not have one. Additionally, I am a consumer of mass media like a majority of the United States population. I find pop culture fascinating and utilize it within my work to make comparisons to my values and perceptions of our society. I primarily work in graphic design because it isn't limiting. It gives me the opportunity to continue to explore all disciplines of art and it is always changing which allows me to continue growing and refining my skills.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.